Medicine, religion, and the body - Coleman, Elizabeth Burns, 1961-; White, Kevin, PhD (International studies in religion and society, 2010)
This book develops an interdiscplinary as well as cross cultural and historical analyses of the relationship between medicine, religion, and the body.